Validitas Media Pembelajaran Berbasis Google Sites untuk Meningkatkan Hasil Belajar Siswa pada Materi Sistem Ekskresi - Pulumoduyo, Siti Nurul Adia; Katili, Abubakar Sidik; Ibrahim, Mustamin; Solang, Margaretha; Husain, Ilyas H. (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Biology learning on excretory system materials often experiences obstacles due to the abstract nature of the material and the lack of use of interactive learning media. As a result, students tend to be passive and learning outcomes are low. This condition shows the need for digital-based learning media innovations that are able to present visualization and interactivity in the learning process. This study aims to determine the level of validity of Google Sites-based learning media on human excretion system materials. The type of research used is research and development with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. However, this study is limited to the limited stage of trials. The research instrument is in the form of validation sheets assessed by material experts and media experts. The results of the study showed that the average validation score by material experts was 94.3% and by media experts was 92.5%, both of which were included in the very valid category. Based on these results, it can be concluded that the Google Sites-based learning media developed is suitable for use as a biology learning medium. This media is effective in helping students understand the concept of the excretory system in a more interesting, contextual, and interactive way.